Complex coupled system dynamics and the global warming policy problem. Issue 2 (2002) - Rosser, J. Barkley
Abstract : A Public Domain, once a velvet carpet of rich buffalo-grass and grama, now an illimitable waste of rattlesnake-bush and tumbleweed, too impoverished to be accepted as a gift by the states within which it lies. Why? Because the ecology of this Southwest happened to be set on a hair trigger.—Aldo Leopold. 1933. The Conservation Ethic. Journal of Forestry 33: 636–637.